Logistic assets and the consequences of their practical use - Krykavskyy, Ye.; Pokhylchenko, О. (Видавництво Львівської політехніки, 2013)
The article scrutinises the specification pertinence of the category “logistic assets” as well as their structures and performance efficiency indices. In particular, the composition of the fixed assets, constituting the main interest from the point of view of Logistics according to the adopted in accounting classification, is determined; the industrial (technological) structure of fixed assets for different types of enterprises from the point of view of Logistics is provided; the composition of current assets constituting the main interest from the point of view of Logistics is analysed. The complex of indices for measuring logistic assets practical use efficiency has been formed in order to evaluate and identify the reserves of logistic assets efficiency increase and improvement of functioning of the logistic system as a whole and all its components. Актуалізована доцільність уточнення категорії «логістичні активи», а також їх структури та показників ефективності використання. Визначено склад основних засобів, які становлять основний інтерес з точки зору логістики стосовно прийнятої у бухгалтерському обліку класифікації, наведено виробничу (технологічну) структуру основних засобів для різних типів підприємств з погляду логістики, проаналізовано склад оборотних активів, які становлять основний інтерес. З метою оцінювання та виявлення резервів підвищення ефективності використання логістичних активів та функціонування загалом логістичної системи та її компонентів сформовано комплекс показників оцінки ефективності їх використання.
Логістичні активи та консеквенції їх використання
Keywords: assets; balance sheet; logistic assets; fixed assets; stock; іndices of logistic assets efficiency; активи; баланс; логістичні активи; основні засоби; запаси; показники ефективності використання логістичних активів